Factors Related to the Nutritional Status of Children in Area Served by the Pattingalloang Health Center, Makassar - Pawenrusi, Esse Puji (Pakistan Journal of Nutrition, 2016)
Malnutrition and under nourishment remain major problems in the health sector, especially in many developing countries. Based on estimates by the WHO, approximately 54% of under-five mortality cases are due to the poor nutritional status of these children. In 2013, approximately 2.66% of all children were malnourished. This research aimed to identify the factors related to the nutritional status of children under five, focusing on the knowledge and attitudes of mothers and on family income. This research is an observational, analytical, cross-sectional study. The population includes all children residing in the area served by the Pattingaloang Health Center, with one-half of all the children who visited the Pattingaloang Health Center, as many as 52 people, sampled by accidental sampling. The study findings show that there are relationship among the knowledge of mothers (p = 0.002), the attitudes of mothers (p = 0.000), the family’s income (p = 0.000) and the nutritional status of these children. In conclusion, there is a relationship among mothers' knowledge and attitudes, family income and children’s nutritional status. It is recommended that parents be more active in seeking information about how to care for their children and provide balanced, nutritious foods from health workers in the health integrated service and health centers, as well as from the mass media.